Antimicrobial potentials of Lantana camara montevidensis leaf extract on wounds infected with Candida isolates - Edim, Sunday Nyambi 1, Ogba, Ofonime Mark 1 *, Anyawu, Stanley 2 and Bebia, Glory Philemon 1 (Sokoto Journal of Medical Laboratory Science)
The use of medicinal plants for therapeutic purposes is a secular tradition in different cultures. The emergence of antimicrobial resistance among microorganisms calls for alternative sources. Plants having antimicrobial activity against multidrug-resistant fungi may be considered good assets. In this study, we investigated the effect of different concentrations of Lantana camara leaf extract against Candida isolates from infected wounds in vitro and in vivo using animal models. Aqueous and methanol extraction was done using Soxhlet apparatus. Candida albicans isolates associated with wound infections were used for the study. Antifungal susceptibility testing was done using the E-Test strips. Male Wistar rats were used for the study. The rats were anesthetized before incision wounds were made. The rats were treated with 100mg/mL, 50mg/mL and 25mg/mL concentration of extract topically. The skin tissues of the sacrificed rats were obtained for histological examination using Haematoxylin and eosin technique. The susceptibility rate of the Candida isolates ranged from (0.0% - 40.0%). Rats treated with 100mg/mL methanol extract had best mean wound contractions of 70.3±0.58 with damaged tissue repair. Methanol extract of Lantana camara leaf had antimicrobial activity and topical healing effect on Candida infected wounds. It could be used as an alternative for Candida wound management.